Integrasi Living Hadis dan Pendidikan Karakter Melalui Metode Storytelling - Istiani, Nurul Istiani (IEMJ: Islamic Education and Management Journal, 2025)
This study aims to describe the concept of character education values contained in various stories in the Hadith through the storytelling method. This qualitative study is in the form of a literature review. Primary and secondary data were obtained from various scientific literature closely related to the main subject matter. This study uses a descriptive approach. Data collection was conducted using documentation techniques. Meanwhile, data analysis was conducted through reduction, presentation, and verification. The results of the study concluded that the moral values contained in various stories in the Hadith can be used as the basis for character education learning through the storytelling method. This shows that living hadith can be synergized with character education learning methods. This study contributes to the importance of creative learning methods to disseminate the values of character building contained in the theological foundations of Islam.